Antiplatelet therapy for patients with stable ischemic heart disease and baseline thrombocytopenia: Ask the hematologist. (September 2014) - Morici, Nuccia; Cantoni, Silvia; Savonitto, Stefano
Abstract Baseline thrombocytopenia (TP) is relatively common in patients referred for percutaneous coronary intervention (PCI). Its detection may have implications for long-term antiplatelet medication prescription and adherence. The aim of this article is to review several practical aspects in managing patients with baseline TP and stable coronary artery disease (CAD). Moving from two clinical cases, we tried to picture cardiological scenarios associated with baseline TP and to provide flow charts for patient's management which take into consideration both the cardiological and the hematological conditions. TP in patients with stable CAD on antiplatelet treatment may follow diverse clinical courses depending upon TP inferred etiology, baseline degree of thrombocytopenia and its time course as outlined by previous complete blood counts, when available. Evaluation of these three parameters may guide the planning of further patient work-up and the choice of the most appropriate cardiological treatment (medical, invasive with stent implantation or coronary artery bypass). A multidisciplinary evaluation comprehensive of hematological counseling is also recommended in these patients before planning prolonged dual anti-platelet therapy.